Analysis of budget spending on social protection: challenges of the COVID-19 pandemic - Dluhopolskyi, Oleksandr; Kozar, Andrii (Herald of Economics, 2022)
Introduction. The inconsistency of the public policy of socio-economic development of Ukraine in recent years, in combination with the latest crisis phenomena, such as the coronavirus epidemic, Russian aggression against Ukraine, have intensified negative trends in various spheres of public life. The preservation of the low standard of living of the population, the significant scale of hidden unemployment, the deepening of the demographic crisis, the social insecurity of the main mass of citizens have become real threats to the national security of the country in various spheres: socio-economic, political, and ecological. The connection of these destructive processes with the lack of thought, inconsistency and half-heartedness of socio-political and economic reforms in Ukraine became an obvious phenomenon, which caused a decrease in the level of trust of the domestic society in the authorities. This caused a significant part of the population to lose faith in the fact that it is generally possible to build a civilized, socially responsible state in Ukraine, which will be able to provide a decent standard of living for its citizens. The consequence of this was labor migration and mass emigration of the most active part of society. The outlined problems deepened even more with the beginning of the full-scale war of the Russian Federation against Ukraine in 2022, which led to a catastrophic drop in the standard of living of a large part of the population, unprecedented scale of displacement of people, destruction of the housing stock, infrastructure and other phenomena that the state did not face during the entire period independence These problems bring to the fore the need for a radical revision of the approaches and principles of regulation of the social sphere and the selection of tools for solving social policy problems.Purpose. To reveal the theoretical foundations and carry out an analysis of budget expenditures for social protection.Methods. The conducted research is based on a dialectical and systemic approach to the knowledge of economic phenomena and processes. Numerous scientific methods of research were used: generalization, systematization, grouping – when revealing the theoretical foundations of social policy, sources, forms and directions of budget expenditures for its implementation; methods of economic analysis, comparison, induction and deduction – when assessing the practice of budget expenditures for social policy and their effectiveness; analysis and synthesis, comparison – when developing directions for improving budget expenditures for social policy in the context of increasing their efficiency. Results. One of the characteristic features of social protection of the population in Ukraine is an excessively “inflated” system of social transfers at the expense of budget funds. Despite significant amounts of funding, the dispersion of resources among many budget programs with low targeting of payments leads to waste. Therefore, an important issue of budget expenditures for social policy is the choice of effective tools for their implementation to ensure the effective use of funds.The dynamics of budget expenditures of all levels for social protection of the population in recent years is characterized by steady growth. In 2021, UAH 367.35 billion of budget funds were allocated for these needs, which is UAH 20.63 billion more than in 2020. In general, for 2018-2021, the amount of budget financing of social protection programs increased 1.2 times. The assessment of the structure of budget expenditures for social protection of the population according to the units of functional classification shows their significant change in 2020-2021, which is a consequence of the change in approaches to the financing of a number of social programs. A significant decrease in funding took place with regard to expenditures on social protection in case of incapacity for work (by 4.6 times), social protection of families, children and youth (by 20.0 times), while expenditures on social protection of other categories of the population increased by 7.3 times. Such significant changes in the structure of expenditures on social protection of the population were provoked by the fact that a number of budgetary social protection programs were transferred from financing from local budgets to direct financing from the state budget.In Ukraine, the vast majority of social transfers are assigned according to a categorical approach due to the lack of effective methods of addressing and checking the real level of need. Because of this, the contingent of recipients of social benefits is too wide, which, in the conditions of limited budgetary resources, forces the government to minimize the amount of social benefits. In our country, the policy of social populism continues to dominate, when the state tries to cover the largest possible contingent of the population with social protection measures, while limiting the size of the transfers themselves. Therefore, the effectiveness of such social programs is doubtful.Discussion. As part of mitigating the negative consequences of the corona crisis at the expense of budget funds, the following social protection innovations have been introduced in Ukraine: simplification of the conditions for participation in the housing subsidy program; liberalization of conditions for receiving unemployment benefits; strengthening of social protection of families with children; additional social protection of pensioners; strengthening of social protection of persons who provide social services. However, the amount of funding of budget programs for social protection of the population, directly caused by measures to combat the coronavirus epidemic, turned out to be insignificant and had a weak impact on the total amount of budget expenditures for social protection of the population.